Comparison of solidification cracking susceptibility between Al-Mg and Al-Cu alloys during welding: A phase-field study. (June 2018) - Geng, Shaoning; Jiang, Ping; Shao, Xinyu; Mi, Gaoyang; Wu, Han; Ai, Yuewei; Wang, Chunming; Han, Chu; Chen, Rong; Liu, Wei
Abstract: Based on two-dimensional phase-field simulations, we demonstrated the possible reasons why Al-Mg alloys can have better resistance to solidification cracking than Al-Cu alloys despite their wide freezing temperature range. Using Al-4.0 wt% Cu and Al-4.0 wt% Mg alloy as examples, we found that back-diffusion is negligible due to the relatively high cooling rate, and extensive coalescence occurs at earlier solidification stage in Al-4.0 wt% Mg alloy compared with Al-4.0 wt% Cu alloy. With considering coalescence predicted by phase-field simulations, the calculated solidification cracking index of Al-Mg alloy is reasonably lower than Al-Cu alloy. Graphical abstract: Unlabelled Image